Adding Value Every Sprint: A Case Study on Large-Scale Continuous Requirements Engineering - Kasauli, Rashidah; Knauss, Eric; Nilsson, Agneta; Klug, Sara (WS on Continuous Requirements Engineering, 2017)
Agile development practices, such as continuous integration and continuous delivery, promise value through shorter time to market and increased exibility. While these practices have been widely adopted in small-scale, they have shown to be challenging to adopt in large-scale, system development. This is often due to a distance between customer and developer in large scale systems, and the need to break down value from the whole system into manageable parts. The notion of value is fundamental for agile methods, especially for practices such as continuous delivery to the customer. However, how value should be handled in development practices is not clearly understood. In this paper, we investigate how the notion of adding value in every sprint has been perceived in a large-scale system development. Based on an exploratory qualitative case study, the outcome shows that it is perceived bene cial by practitioners although it comes at a price and challenges exist.
Keywords: Value; Continuous requirements engineering; Continuous integration; Continuous delivery; Large-scale agile